Psychological testing and assessment an introduction to tests and measurement - Cohen, Ronald Jay; Swerdlik, Mark E. (McGraw-Hill, 2013)
Cohen, a clinical psychologist, et al. acquaint beginning students with psychological testing and assessment. They provide an overview of the field, its tools, and historical, cultural, and legal/ethical considerations, then discuss basic statistical principles; reliability; validity; utility; test development; intelligence and personality assessment, including school-related assessments; clinical, counseling, and neuropsychological assessment; and instruments used in career choice and transition. This edition has updated discussions of instruments; updated information about test-related legislation, judicial decisions, and administrative regulations; and new and updated coverage of the new edition of the Diagnostic and Statistical Manual of Mental Disorders, new psychological tools such as fMRI, response to intervention, the concepts of successful intelligence and visual-object intelligence, a new measure for evaluating the internal consistency of a test called the average proportional distance, information on assessment in ancient Egypt, conditions that might prompt a neuropsychological evaluation, and the use of the nominal distinction between objective and projective assessment. It also has expanded discussion of the Flynn effect, the Minnesota Multiphasic Personality Inventory-2, the timeline followback method in behavioral assessment, competency to stand trial, systematic vs. random error in measurement, test validation strategies, classical test theory in comparison to item response theory, nature vs. nurture factors in measured intelligence, and the purpose of educational assessment within the context of current legislation. It has more glossary and self-assessment terms and critical thinking features. Annotation ©2012 Book News, Inc., Portland, OR (booknews.com)